2012
DOI: 10.1136/emermed-2012-201652
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for difficult peripheral venous access: systematic review and meta-analysis

Abstract: Ultrasound guidance increases the likelihood of successful peripheral cannulation in difficult access patients. We recommend its use in patients who have difficult venous access, and have failed venous cannulation by standard methods. Further randomised controlled trials (RCTs) with larger sample sizes would be of benefit to investigate if Ultrasound has any additional advantages in terms of reducing the procedure time and the number of skin punctures required for successful venous cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 31 publications
(42 reference statements)
4
137
0
7
Order By: Relevance
“…[12] They found US guidance increased the likelihood of successful cannulation in difficult-access patients, just as the original studies had found (Odds ratio 2.42; 95% confidence interval 1.26-4.68).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…[12] They found US guidance increased the likelihood of successful cannulation in difficult-access patients, just as the original studies had found (Odds ratio 2.42; 95% confidence interval 1.26-4.68).…”
Section: Introductionmentioning
confidence: 62%
“…The increased success rate is in agreement with other studies. [6,8,12,16,18] In comparison with the BP group with low satisfaction, patients with difficult IV access who were cannulated by ultrasonographic guidance showed a higher satisfaction score. (Mean of 2.88, SD 1.025, 't' 2.049 and 'p' 0.049) ( Table 2, Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews have demonstrated that US-guidance increases the success rate of peripheral venous cannulation [5][6][7]. Peripheral venous access under sonographic guidance is safe in adults and in pediatric patients as well [8][9][10], with an overall success rate of 91% and a successful first attempt in 73% of the cases [11].…”
Section: Technique and Resultsmentioning
confidence: 99%
“…[1][2][3] The Agency for Healthcare Research and Quality declared the use of ultrasound a requisite adjunct for patient safety during all central line placements, and ultrasound use has been enthusiastically endorsed for this purpose for many years. 4 Peripheral IV access using ultrasound (PIVUS) has also been studied with no appreciable difference in ability or efficacy among emergency department physicians, physician assistants, registered nurses (RNs), or technicians.…”
Section: Introductionmentioning
confidence: 99%